Predicting parental support and parental perceptions of child and youth movement behaviors. (March 2019) - Rhodes, Ryan E.; Stearns, Jodie; Berry, Tanya; Faulkner, Guy; Latimer-Cheung, Amy E.; O'Reilly, Norman; Tremblay, Mark S.; Vanderloo, Leigh; Spence, John C.
Abstract: Objectives: In light of a shift to considering the integration of movement behaviors, the purpose of this study was to examine an extended multi-component theory of planned behavior (TPB) framework to predict parent support and parent perceived behavior of the Canadian 24-h movement behaviors in children and youth including light physical activity (LPA), moderate to vigorous physical activity (MVPA), sleep, and screen-time. Design: Cross-sectional survey. Method: A representative sample of Canadian parents (N = 1208) with children aged 5–17 years of age, completed measures of TPB, support behaviors, and the four child health behaviors via a panel survey. Results: Controlling for child age, structural equation models showed that child health behavior was predicted by parental support of that behavior (10–27% of variance explained) and intention and perceived capability to support explained support behaviors (42–53% variance explained). The TPB antecedents of intention, however, differed by each health behavior. Conclusions: Parental support behaviors are related to perceived child/youth behavior. Parental support is partly dependent on intention and perceptions of parental capability but the interventions to promote the underlying social cognitions behind parental support may be different for MVPA, LPA, sleep, and screen time restriction. Highlights: First study to explore parental support of the 24-h movement behaviors for children and youth. Child health behavior was predicted by parental support of that behavior (10–27% of variance explained). Intention and perceived capability to support explained support behaviors (42–53% variance explained). Antecedents of intention differed by each health behavior. There were almost no differences in the models whether the parents were considering youth or children.